Las dimensiones políticas de Heidegger en la trilogía: Pueblo-Lenguaje-Ser (2007)
The German thinker Martin Heidegger never wrote about politics, so it is difficult to find references or reflections on politics in its extensive oeuvre. The purpose is to show the political dimensions of Heidegger based on interpretation condensed in the trilogy land-language-being; that is evident inhis work. There is an episode in the life of the German thinker when he was rector of the University of Freiburg in 1933, which condemns him to be politically linked to National Socialism. This fact has generated controversy and reactions to the proposal of Heidegger in thinking. Two of these will beshown; one against and another with Heidegger to show the different and conflicting reactions to Heidegger’s proposal. Finally, attempt is made to show that the trilogy land-language-being couldhelp resolve fissures in policies that generate violence in towns today.